Profiling hippocampal neuronal populations reveals unique gene expression mosaics reflective of connectivity-based degeneration in the Ts65Dn mouse model of Down syndrome and Alzheimer’s disease - Alldred, Melissa J.; Ibrahim, Kyrillos W.; Pidikiti, Harshitha; Lee, Sang Han; Heguy, Adriana; Chiosis, Gabriela; Mufson, Elliott J.; Stutzmann, Grace E.; Ginsberg, Stephen D. (Frontiers in Molecular Neuroscience, 2025)
IntroductionIndividuals with Down syndrome (DS) exhibit neurological deficits throughout life including the development of in Alzheimer’s disease (AD) pathology and cognitive impairment. At the cellular level, dysregulation in neuronal gene expression is observed in postmortem human brain and mouse models of DS/AD. To date, RNA-sequencing (RNA-seq) analysis of hippocampal neuronal gene expression including the characterization of discrete circuit-based connectivity in DS remains a major knowledge gap. We postulate that spatially characterized hippocampal neurons display unique gene expression patterns due, in part, to dysfunction of the integrity of intrinsic circuitry.MethodsWe combined laser capture microdissection to microisolate individual neuron populations with single population RNA-seq analysis to determine gene expression analysis of CA1 and CA3 pyramidal neurons and dentate gyrus granule cells located in the hippocampus, a region critical for learning, memory, and synaptic activity.ResultsThe hippocampus exhibits age-dependent neurodegeneration beginning at 6 months of age in the Ts65Dn mouse model of DS/AD. Each population of excitatory hippocampal neurons exhibited unique gene expression alterations in Ts65Dn mice. Bioinformatic inquiry revealed unique vulnerabilities and differences with mechanistic implications coinciding with onset of degeneration in this model of DS/AD.ConclusionsThese cell-type specific vulnerabilities may underlie degenerative endophenotypes suggesting precision medicine targeting of individual populations of neurons for rational therapeutic development.